Glycosphingolipids in Filamentous Fungi: Biological Roles and Potential Applications in Cosmetics and Health Foods - Jiang, Chunmiao; Ge, Jinxin; He, Bin; Zeng, Bin (Frontiers in Microbiology, 2021)
Filamentous fungi are a group of economically important fungi used in the production of fermented foods, industrial enzymes, and secondary metabolites. Glycosphingolipids (GSLs) as constituents of lipid rafts are involved in growth, differentiation, and response to environment stress in filamentous fungi. In addition to these key roles, GSLs are also important in the barrier function of skin to retain moisture as a moisturizing ingredient in cosmetics or health products for their strong biological activity as a functional component. GSLs found in filamentous fungi are divided in two major classes: neutral GSLs (glycosylceramides), glucosylceramides (GlcCers) and/or galactosylceramides (GalCers) and acidic GSLs, mannosylinositol phosphorylceramide (MIPC) and mannosyldiinositol phosphorylceramide [M(IP)2C]. Glycosylceramides are one of the abundant GSLs in Aspergillus and known to improve skin-barrier function and prevent intestinal impairment as a prebiotic. Some filamentous fungi of Aspergillus spp., synthesizing both GlcCer and GalCer, would be an amenable source to exploit glycosylceramides that wildly adding in cosmetics as moisturizing ingredients or health food as dietary supplements. In this minireview, the types, structures, and biosynthetic pathways of GSLs in filamentous fungi, and the relevance of GSLs in fungal growth, spore formation and environmental stress response are explained. Furthermore, the advantage, potential development, and application of GlcCer and GalCer from filamentous fungi Aspergillus spp. are also investigate based on the use of plant GlcCer in health foods and cosmetics.